Globalizing Roman culture : unity, diversity and empire - Hingley, Richard (Routledge, 2005)
A study of identity and social change in the Roman empire and the relationship of this knowledge to understanding of the contemporary world.
Keywords: Rome -- Civilization -- Influence.; Acculturation -- Rome.; Rome -- Civilisation -- Influence.; Éducation au développement -- Rome.; HISTORY -- Ancient.; Acculturation; Civilization -- Influence; Rome (Empire)